A historical review and bibliometric analysis of disruptive innovation. Issue 2 (3rd April 2019) - Shang, Tiantian; Miao, Xiaoming; Abdul, Waheed
Abstract : Purpose: The purpose of this paper is to demonstrate visually the knowledge structure and evolution of disruptive innovation. The paper used CiteSpace III to analyze 1, 570 disruptive innovation records from the Web of Science database between 1997 and 2016. Design/methodology/approach: Initially, this paper offers a comprehensive overview of papers, countries, journals, scholars and application areas. Subsequently, a time zone view of high-frequency keywords is presented, emphasizing the course of evolution of the study hotspots. Finally, a visualization map of cited references and co-citation analysis are provided to detect the knowledge base at the forefront of disruptive innovation. Findings: The findings are as follows: the number of papers shows exponential growth. The USA has the largest contribution and the strongest center. The Netherlands shows the largest burst, followed by Japan. Journal of Production Innovation Management and Research Policy is the most important journals. Hang CC has the largest number of articles. Walsh ST is identified as a high-yielding scholar. Christensen CM is the most authoritative scholar. Engineering electrical electronic is the most widely used research category, followed by management and business. The evolutionary course of the study hotspots is divided into five stages, namely, start, burst, aggregation, dispersion and not yet formed. Eight key streams in the literature are extracted to summarize the knowledge base at the forefront of disruptive innovation. Originality/value: This paper explores the whole picture of disruptive innovation research and demonstrates a visual knowledge structure and the evolution of disruptive innovation. It provides an important reference for scholars to capture the current situation and influential trends in this field.